Religion Past and Present online: RPP (Brill, 2011)
Religion Past and Present (RPP) Online is the online version of the updated English translation of the 4th edition of the definitive encyclopedia of religion worldwide: the peerless Religion in Geschichte und Gegenwart (RGG). This great resource, now at last available in English and Online, Religion Past and Present Online continues the tradition of deep knowledge and authority relied upon by generations of scholars in religious, theological, and biblical studies. Including the latest developments in research, Religion Past and Present Online encompasses a vast range of subjects connected with religion.
Gesehen am 10.03.23
Keywords: Datenbank; Religionswissenschaft; Religion; Theologie